2019
DOI: 10.1186/s40645-019-0308-8
|View full text |Cite
|
Sign up to set email alerts
|

Climatic reconstruction at the Sannai-Maruyama site between Bond events 4 and 3—implication for the collapse of the society at 4.2 ka event

Abstract: The Jōmon period/culture corresponds to the Neolithic period/culture in Japanese prehistory. The Sannai-Maruyama site (5.9-4.2 cal. kyr BP), the most famous, the largest, and the well-studied mid-Holocene (mid-Jōmon) archeological site inhabited by hunter-gatherers with sedentary lifestyle in northern Japan, started at early Bond event 4 and collapsed at late Bond event 3 (4.2 cal. kyr BP at the boundary between mid-Holocene, Northgrippian, and late-Holocene, Meghalayan), synchronous with the decline of the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…The SST was reconstructed based upon the analysis of C37 alkenone. The major alkenone-producing coccolithophorid was Emiliania huxleyi in this area under both the Tsugaru and Oyashio currents (Hagino et al, 2005;Kawahata et al, 2017a;Kawahata, 2019). The major production period of E. huxleyi has been observed in satellite images in summer (June -August) (Takahashi et al, 1995), which is confirmed by the sediment trap experiment at Site MD01-2409 (41°33.8', 141°52.0'E) under the influences by the Tsugaru current ( Fig.…”
Section: C37 Alkenone Sstsupporting
confidence: 73%
See 1 more Smart Citation
“…The SST was reconstructed based upon the analysis of C37 alkenone. The major alkenone-producing coccolithophorid was Emiliania huxleyi in this area under both the Tsugaru and Oyashio currents (Hagino et al, 2005;Kawahata et al, 2017a;Kawahata, 2019). The major production period of E. huxleyi has been observed in satellite images in summer (June -August) (Takahashi et al, 1995), which is confirmed by the sediment trap experiment at Site MD01-2409 (41°33.8', 141°52.0'E) under the influences by the Tsugaru current ( Fig.…”
Section: C37 Alkenone Sstsupporting
confidence: 73%
“…In Funka Bay, alkenone SSTs (ATs) showed definite cooling by 2-3°C at this event. Kawahata (2019) discussed the climatic mechanism behind the event based upon the environmental factors in Mutsu Bay, and concluded that southward shift of the westerly jet, in association with a weakened East Asian Summer Monsoon, could cause a relatively cool climate.…”
Section: 2ka Event In Funka Baymentioning
confidence: 99%
“…This is consistent with previous findings showing that the linea aspera of the femur of an Initial Jomon man excavated from Futsukaichi cave (Futsukaichi city, Oita Prefecture, Japan), which is in the vicinity of Hegi cave, was not developed [ 36 ]. The period from 4,000 to 4,500 years ago, which was defined as the Late Jomon Period in the present study, was a time of decreasing temperatures in the Holocene world [ 21 ]. This was a time when it became difficult to obtain food, and many settlements in other parts of Japan were reported to have disappeared [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Late Holocene is dated to the Late Jomon Period, while the other groups are roughly dated to the Initial/Early Jomon Period. In the Holocene, which began with the end of the Ice Age, the Late Holocene is the period during which temperatures dropped and many settlements disappeared [ 20 , 21 ]. Changes in the living environment may be reflected not only by comparisons between modern humans and the prehistoric remains excavated from Hegi cave but also differences in the ages of the prehistoric remains.…”
Section: Introductionmentioning
confidence: 99%
“…N. stella is well established as indicator taxon for low‐oxygen conditions (e.g., Bernhard et al., 1997). Nevertheless, it has been rarely used for geochemistry‐based paleoceanographic reconstructions (Altenbach et al., 2012; Kawahata, 2019) and its TE composition has not previously been studied. Here we pair in a multi‐technique approach SIMS in situ TE analyses, to determine the concentration of Mn, Mg and Sr, with state‐of‐the‐art synchrotron radiation‐based scanning XRF (X‐ray fluorescence) multilength scale imaging, to map the Mn and Ca distribution in selected foraminiferal tests in high resolution.…”
Section: Introductionmentioning
confidence: 99%